2019
DOI: 10.56093/ijas.v89i8.92846
|View full text |Cite
|
Sign up to set email alerts
|

Effect of micronutrients (Fe and Zn) on flowering and yield attributes of chrysanthemum (Chrysanthemum morifolium) cv. Mayur 5

Abstract: A field experiment was carried out to study the effect of zinc and iron on growth, yield and quality of chrysanthemum (Chrysanthemum morifolium Ramat. ) cv. Mayur 5 during 2016 and 2017. The experiment was laid out in randomized block design with three replications comprising nine levels of micronutrients, i. e. control (T1), ZnSO4 @ 0. 1% (T2), ZnSO4 @ 0. 2% (T3), ZnSO4 @ 0. 5% (T4), FeSO4 @ 0. 2% (T5), FeSO4 @ 0. 5% (T6), FeSO4 @ 0. 8% (T7), FeSO4 + ZnSO4 @ 0. 5% each (T8) and FeSO4 + ZnSO4 @ 0. 7% each (T9)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…and Abu El-Ghait, et al, (2020) on Jasminum sambac showed that the heaviest flower weight/plant was recorded by BA at 60 ppm + mineral fertilization at 6 g/pot on both seasons. Patokar, et al (2017) on Tagetes erecta L., Vanlalruati et al (2019) on Chrysanthemum morifolium, Mohana, et al (2021) on Tagetes erecta L., Kurbah and Fatmi (2022) on Dianthus caryophyllus L., Thakur et al (2022) on the chrysanthemum morifolium, Sultana, et al (2022) on Lisianthus, Kalantara Ahmadi and Danishian (2023) on Brassica napus L. 33 30.33 30.33 30.33 198.33 200.67 199.50 196.66 193.33…”
Section: Effect Of Planting Date Growth Stimulants and Their Combinat...mentioning
confidence: 99%
“…and Abu El-Ghait, et al, (2020) on Jasminum sambac showed that the heaviest flower weight/plant was recorded by BA at 60 ppm + mineral fertilization at 6 g/pot on both seasons. Patokar, et al (2017) on Tagetes erecta L., Vanlalruati et al (2019) on Chrysanthemum morifolium, Mohana, et al (2021) on Tagetes erecta L., Kurbah and Fatmi (2022) on Dianthus caryophyllus L., Thakur et al (2022) on the chrysanthemum morifolium, Sultana, et al (2022) on Lisianthus, Kalantara Ahmadi and Danishian (2023) on Brassica napus L. 33 30.33 30.33 30.33 198.33 200.67 199.50 196.66 193.33…”
Section: Effect Of Planting Date Growth Stimulants and Their Combinat...mentioning
confidence: 99%